2004
DOI: 10.1080/10284150410001710410
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Supplemented Diet: Effects on Object Recognition Memory and Nuclear Factor-kappa B Levels in Aged Rats

Abstract: It has been reported that an antioxidant-rich, blueberry-supplemented rat diet may retard brain aging in the rat. The present study determined whether such supplementation could prevent impaired object recognition memory and elevated levels of the oxidative stress-responsive protein, nuclear factor-kappa B (NF-kappaB) in aged Fischer-344 rats. Twelve aged rats had been fed a 2% blueberry supplemented diet for 4 months prior to testing. Eleven aged rats and twelve young rats had been fed a control diet. The rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(137 citation statements)
references
References 60 publications
8
128
0
1
Order By: Relevance
“…When compared to the control group, all diet-supplemented groups showed improved working memory (short-term memory) performance in the Morris water maze (MWM) ). Short-term 2 % BB supplementation in aged rodents was also found to be effective in reversing cognitive declines in an object recognition task (Goyarzu et al 2004;Malin et al 2011). Subsequent experiments in our laboratory found similar protective effects against agerelated behavioral declines with blackberries (Shukitt-Hale et al 2009a, b), cranberries (Shukitt-Hale et al 2005), black currants (Shukitt-Hale et al 2005), Concord grape juice , plum juice (ShukittHale et al 2009a, b), and walnuts (Willis et al 2009).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…When compared to the control group, all diet-supplemented groups showed improved working memory (short-term memory) performance in the Morris water maze (MWM) ). Short-term 2 % BB supplementation in aged rodents was also found to be effective in reversing cognitive declines in an object recognition task (Goyarzu et al 2004;Malin et al 2011). Subsequent experiments in our laboratory found similar protective effects against agerelated behavioral declines with blackberries (Shukitt-Hale et al 2009a, b), cranberries (Shukitt-Hale et al 2005), black currants (Shukitt-Hale et al 2005), Concord grape juice , plum juice (ShukittHale et al 2009a, b), and walnuts (Willis et al 2009).…”
Section: Introductionmentioning
confidence: 65%
“…A 2 % (w/w) Montmorency tart cherry dose was chosen based on previous studies in humans (Kelley et al 2006), as well as those conducted in our laboratory demonstrating the beneficial effects of phytochemical-rich berry fruits (i.e., blueberry, strawberry, cranberry, blackberry, black currant, and boysenberry) on cognition, motor function, and suppression of inflammation and oxidative stress in aged animals and accelerated aging models (Casadesus et al 2004;Goyarzu et al 2004;Shukitt-Hale et al 2005;Galli et al 2006;Shukitt-Hale et al 2007, 2009aMalin et al 2011). The amount of ground corn was adjusted in the control diet to compensate for the added volume of the freeze-dried cherry powder, in accordance with established methodology (ShukittHale et al 1998;Youdim et al 2000).…”
Section: Dietmentioning
confidence: 99%
“…The amount of corn in the control diet was adjusted to compensate for the added volume of the coffee powder or caffeine. The control NIH-31 diet was the same as that used in earlier studies in which other foods were found to be beneficial for mitigating brain aging (Youdim et al 2000;Joseph et al 2003;Casadesus et al 2004;Goyarzu et al 2004;Shukitt-Hale et al 2005). The coffee powder, supplied by Kraft Foods Global, Inc. (Northfield, IL, USA), was prepared by lyophilizing brewed coffee.…”
Section: Dietsmentioning
confidence: 99%
“…Although the mechanisms by which flavonoids act in the brain remain a source of debate, a substantial number of flavonoid supplementation studies in animal models has provided important clues to their function. Investigations have pointed to many potential mechanisms, including the regulation of oxidative stress signals such as NF-kB (150) , enhancement of neuroprotective stress shock proteins (151) and anti-inflammatory actions through the regulation of the expression of specific inflammatory genes (IL-1b, TNFa) (152) . In the following sections, we will focus on the potential of flavonoids to modulate and influence the molecular architecture responsible for learning and memory in the brain and how such activity may underpin behavioural changes induced by flavonoid-rich diets and pure compounds.…”
Section: The Impact Of Flavonoid-rich Foods On Memory and Learningmentioning
confidence: 99%